Pemberdayaan Kewirausahaan Masyarakat Kampung Dusun Pusaka Melalui Inovasi Spray Anti-Nyamuk dari Serai - Marta, Auradian; Fakhrul, Muhammad; Rahman, Sauqina Alwafi; Fella, Fella; Lestari, Winda; Silva, Yana; Saidori, Amanda; Putri, Nadya Zahara; Bizikrillah, Wahyu Arif; Ginting, Randi Malik; Meliyana, Etika; Simanjuntak, Aloysius Wisely; Mulyono, Sigit (Abdimas Indonesian Journal, 2024)
This article discusses a community empowerment program in Kampung Dusun Pusaka that focuses on entrepreneurship development through the utilization of lemongrass as the main ingredient in making anti-mosquito spray. The program was designed to foster entrepreneurial spirit while providing practical skills in making useful products at the local level, given the low interest of residents in entrepreneurship. In this activity, residents were introduced to the benefits of lemongrass, especially its citronella content which is proven to be effective as a mosquito repellent and environmentally friendly. The program involved theoretical sessions on entrepreneurship, SWOT analysis, and business planning strategies, followed by hands-on training in making anti-mosquito sprays. The methods used were lectures, question and answer discussions, and practice. The results showed high enthusiasm from the community in attending the training, learning the techniques taught, and applying them independently. In conclusion, the program successfully empowered the community with the ability to address health and economic challenges, and encouraged sustainable practices. The program also demonstrated how the integration of local resources with entrepreneurship training can support the improvement of village welfare.